2020
DOI: 10.1186/s41938-020-00269-2
|View full text |Cite
|
Sign up to set email alerts
|

Natural infection potential and efficacy of the entomopathogenic fungus Beauveria bassiana against Orosanga japonica (Melichar)

Abstract: In this study, potential of the entomopathogenic fungi (EPF) isolates from dead samples of Orosanga japonica (Melichar) (Hemiptera: Ricaniidae) was evaluated. Infected specimens with fungi results confirmed that the samples were Beauveria bassiana after morphological and molecular identification. Amplicons produced two haplotypes (h = 2), which included one polymorphic site after sequence and named isolates 1 and 2. Two haplotypes were rooted with MK229193.1, MG345084.1 B. bassiana Genbank samples. Two-year su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…Considering the LT 50 and LT 90 values, B. bassiana isolates were slightly more effective at 25 than at 20 °C, which put forward some B. bassiana isolates as significant candidate organisms for controlling O. japonica in the origin region of the country. Akıner et al (2020) found that the lowest LT 50 values for B. bassiana isolate-1 and isolate-2 were 2.92 and 2.56 days, respectively, for nymphs using the leaf dipping method at (1 × 10 6 conidia ml -1 ). In addition, EPF isolates with a high virulence and good growth characteristics are the basis in pest biocontrol.…”
Section: Isolate Code 20 °C 25 °Cmentioning
confidence: 93%
See 4 more Smart Citations
“…Considering the LT 50 and LT 90 values, B. bassiana isolates were slightly more effective at 25 than at 20 °C, which put forward some B. bassiana isolates as significant candidate organisms for controlling O. japonica in the origin region of the country. Akıner et al (2020) found that the lowest LT 50 values for B. bassiana isolate-1 and isolate-2 were 2.92 and 2.56 days, respectively, for nymphs using the leaf dipping method at (1 × 10 6 conidia ml -1 ). In addition, EPF isolates with a high virulence and good growth characteristics are the basis in pest biocontrol.…”
Section: Isolate Code 20 °C 25 °Cmentioning
confidence: 93%
“…The Eastern Black Sea region receives frequent rainfall and characterized by high humidity and low temperatures throughout the year. These environmental conditions are ideal for the development of EPFs such as B. bassiana and Lecanicillium muscarium Zare and Gams (Ascomycota: Hypocreales) (Akıner et al 2020). Conidia of EPFs need moisture for germination and subsequent sporulation; some even require high humidity to initiate infection.…”
Section: Isolate Code 20 °C 25 °Cmentioning
confidence: 99%
See 3 more Smart Citations